Voltage- and transmitter-gated currents of all-amacrine cells in a slice preparation of the rat retina - Boos, R (J Neurosci, 1993)
All-amacrine cells are crucial interneurons in the rod pathway of the mammalian retina. They receive input synapses from rod bipolar cells and make electrical output synapses into the ON-pathway and glycinergic chemical synapses into the OFF-pathway. Whole-cell currents from more than 50 voltage-clamped All-amacrine cells were recorded in a slice preparation of the rat retina. The recorded cells were identified by intracellular staining with Lucifer yellow. Spike-like potentials could be elicited upon depolarization by current injection. A voltage- activated, fast, TTX-sensitive, inward Na+ current was identified. A prominent outward K+ current could be suppressed by tetraethylammonium. GABA as well as glycine activated Cl- channels, which could be blocked by bicuculline and strychnine, respectively. Four agonists of excitatory amino acid receptors--kainate (KA), AMPA, 2-amino-4- phosphonobutyrate (APB), and NMDA--were tested. Inward currents at holding potentials of VH = -70 mV were found by application of KA and AMPA but not by application of APB and NMDA. These currents could be blocked by 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX). ACh did not evoke any current responses.